Analisis Faktor-Faktor yang Mempengaruhi Tingkat Kemiskinan di Kota Banjarmasin - Aprianto, Dwi Teguh (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This research proposes the influence of unemployment rate, PDRB, andeducation level to the poverty level in Banjarmasin city year 2002-2016. Poverty isone of the problems in economic development. Therefore, this study measure howbig the poverty level and the factors that influence its policies to overcome thepoverty city of Banjarmasin. The scope of this study covers poverty conditions in Banjarmasin City. Byanalyzing for 15 years. Multiple linear regression analysis methods. By using theR-Square Test (R2), Simultaneous Test (F Test), and Individual Test (t-test). Unemployment, PDRB, and education together affect poverty. The effect ofthe unemployment rate and the level of education has no significant impact onpoverty. At the same time, PDRB has a substantial impact on poverty inBanjarmasin City. The most dominant factor affecting poverty is PDRB.